The role of internal marketing in job satisfaction: Effects on the selfperceived productivity of bank employees in Latin America - Villavicencio, María Fernanda (2026)
The impact of internal marketing (IM) practices as a strategic driver of employees' perceived productivity has been sidelined in the marketing literature, especially in the context of emerging economies. This study therefore examines the relationships between rewards, internal marketing, job satisfaction, and employees' perceived productivity. Data were collected from a sample of 411 bank employees in Ecuador, Colombia, Mexico, Chile, and Argentina. The results of the structural equation modeling (SEM) indicate that internal marketing, together with financial and psychological rewards, is a significant predictor of job satisfaction, which in turninfluences self-perceived productivity. This study offers significant value to marketers and managers seeking to enhance employee performance and commitment. This research not only enriches IM theory by validating its role in the results chain, but also provides banking marketing and HR managers in Latin America with a roadmap for improving internal satisfaction and performance.